The Cross-Cultural Invariance of the Servant Leadership Survey: A Comparative Study across Eight Countries - Van Dierendonck, Dirk; Sousa, Milton; Gunnarsdottir, Sigrun; Bobbio, Andrea; Hakanen, Jari; Verdorfer, Armin Pircher; Rodriguez-Carvajal, Raquel (Administrative Sciences, 2017)
WOS: 000418117900001 This paper tests and confirms the cross-cultural equivalence of the Servant Leadership Survey (SLS) in eight countries and languages: The Netherlands, Portugal, Germany, Iceland, Italy, Spain, Turkey and Finland. A composite sample consisting of 5201 respondents from eight countries that all filled out the SLS was used. A three-step approach was adopted to test configural invariance, measurement equivalence, and structural equivalence. For the full 30-item version of the SLS, configural invariance and partial measurement equivalence were confirmed. Implications of these results for the use of the SLS within cross-cultural studies are discussed.